(untitled) (Medicine Today, 2023)
Introduction: Chronic venous disease (CVD) is mostly underdiagnosed diseasewhich may progress to chronic venous insufficiency and venous ulcer thus extensive treatment. CVD may affect negatively into patient’sgood well-beingwhich can create burdens on their life and also healthcare resources. Bangladesh has very minimum awareness on CVD. Materials and Methods: This was a cross-sectional study was carried out in department of vascular surgery of National Institute of Cardiovascular disease. we randomly choose 60 patients with chonic venous disease (CVD) and evaluate their characteristics and prevalence of several types along with the management pattern. Data collection started from May 2021 for next 6 months. Results: The patients of this survey were aged between 24 to 70 years and the Mean±SD age was 43.6±12.2. 78.3% of total study population were male, 33.3% were businessman and 10% were housewife. 66.6% patients were having low socio-economic condition. C2 varicose veins were highly prevalent among the study population ( 35%) & lowest prevalence of C4b lipodermatosclerosis or atrophie blanche (11.7%). Male were predominantly more prevalent to having CVD, 78.33% (n47), (p <0.001). Among all the patient 68.3% patient were exposed to smoking. All the patient were managed predominantly by compression therapy mainly are of moderate pressure (66.7%,) 80% of total patients got treated by oral MPFF therapy. Conclusion: : Patients having CVD, invariably presented with the complains of heaviness of leg and unexplained leg swelling and Varicose vein were highly prevalent irrespective of sex. Compression therapy has been remained the mainstay of treatment in tertiary level hospital NICVD along with oral MPFF therapy. Medicine Today 2023 Vol.35(1): 31-33